2020
DOI: 10.1186/s12964-019-0494-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles originating from glioblastoma cells increase metalloproteinase release by astrocytes: the role of CD147 (EMMPRIN) and ionizing radiation

Abstract: Background: Glioblastoma multiforme is an aggressive primary brain tumor that is characterized by local invasive growth and resistance to therapy. The role of the microenvironment in glioblastoma invasiveness remains unclear. While carcinomas release CD147, a protein that signals for increased matrix metalloproteinase (MMP) release by fibroblasts, glioblastoma does not have a significant fibroblast component. We hypothesized that astrocytes release MMPs in response to CD147 contained in glioblastoma-derived ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Astrocytes cultured with GBM EVs show enhanced secretion of immunosuppressive cytokines such as CSF2 and interleukins 4, 10 and 13, thus providing a tumor supportive microenvironment. EVs secreted by irradiated GBM cells have enhanced presence of CD147, which in turn stimulates increased MMP9 release from recipient astrocytes, suggesting the contribution of astrocyte signaling in promoting GBM invasiveness, particularly in response to ionizing radiation [ 229 ] . A recent study reported that GSC EVs induce metabolic reprogramming of pre-transformed astrocytes to enhance proliferation, self-renewal and tumor growth in a mouse allograft model [ 230 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes cultured with GBM EVs show enhanced secretion of immunosuppressive cytokines such as CSF2 and interleukins 4, 10 and 13, thus providing a tumor supportive microenvironment. EVs secreted by irradiated GBM cells have enhanced presence of CD147, which in turn stimulates increased MMP9 release from recipient astrocytes, suggesting the contribution of astrocyte signaling in promoting GBM invasiveness, particularly in response to ionizing radiation [ 229 ] . A recent study reported that GSC EVs induce metabolic reprogramming of pre-transformed astrocytes to enhance proliferation, self-renewal and tumor growth in a mouse allograft model [ 230 ] .…”
Section: Introductionmentioning
confidence: 99%
“…In response to IR, glioblastoma cells increase the levels of CD147 shed in EVs. This protein, involved in regulation of MMPs, enhances MMP9 release from astrocytes exposed to these EVs by increasing JNK signaling, a process that was blocked by knocking out CD147 in glioma cells [69]. Since MMPs break down ECM, this result supports a tumor microenvironment-mediated role of CD147 in glioblastoma invasiveness, and reveals a prominent role for IR, used in treatment for glioblastoma, in enhancing this effect [69].…”
Section: Box 1 Co-culturing Astrocytes With Glioma Cells To Study Cel...mentioning
confidence: 79%
“…This protein, involved in regulation of MMPs, enhances MMP9 release from astrocytes exposed to these EVs by increasing JNK signaling, a process that was blocked by knocking out CD147 in glioma cells [69]. Since MMPs break down ECM, this result supports a tumor microenvironment-mediated role of CD147 in glioblastoma invasiveness, and reveals a prominent role for IR, used in treatment for glioblastoma, in enhancing this effect [69]. In addition, astrocytes exposed to glioblastoma-derived EVs were tested in an 'invadopodia' assay to determine the effects on astrocyte migration and ECM degradation [65].…”
Section: Box 1 Co-culturing Astrocytes With Glioma Cells To Study Cel...mentioning
confidence: 99%
“…A study showed that a distinct astrocytic phenotype is caused by the coexistence of microglia and astrocytes in the tumor environment, which leads to a large release of antiinflammatory cytokines such as TGF-β, IL-10 and G-CSF [83]. RAs increase the expression levels of MMP9, which promotes the tumor invasiveness by breaking down the ECM [84]. After radiation, RAs will increase the secretion of transglutaminase 2 (TG2), which triggers the MES trans-differentiation of GSCs [85,86].…”
Section: Astrocytesmentioning
confidence: 99%